2009
DOI: 10.1038/labinvest.2009.22
|View full text |Cite
|
Sign up to set email alerts
|

Indoleamine 2,3-dioxygenase overexpression causes kynurenine-modification of proteins, fiber cell apoptosis and cataract formation in the mouse lens

Abstract: Indoleamine 2,3-dioxygenase (IDO) is the first enzyme in the kynurenine pathway. The kynurenines formed in this pathway chemically modify proteins and cause apoptosis in cells. Evidence suggests that kynurenines and their protein modifications are involved in cataract formation, but this has yet to be directly demonstrated. We generated transgenic mouse lines (Tg) that overexpress human IDO in the lens. Homozygous Tg (homTg) lenses had higher IDO immunoreactivity, ~4.5 times greater IDO mRNA, and ~8 times high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 59 publications
2
33
0
Order By: Relevance
“…This inhibition of proliferation was reversed by 1-DL-MT treatment [581]. In contrast, when compared with lens epithelial cells, mouse lens fibre cells overexpressing human IDO1 are more susceptible, with IDO1-mediated fibre cell apoptosis evident even in pre-cataract lenses [591].…”
Section: Age-related Cataractsmentioning
confidence: 95%
See 1 more Smart Citation
“…This inhibition of proliferation was reversed by 1-DL-MT treatment [581]. In contrast, when compared with lens epithelial cells, mouse lens fibre cells overexpressing human IDO1 are more susceptible, with IDO1-mediated fibre cell apoptosis evident even in pre-cataract lenses [591].…”
Section: Age-related Cataractsmentioning
confidence: 95%
“…Protective [102,294,295] Mouse kidney transplant model Protective [298] Rat and mouse liver transplant model Protective [299], not involved [305] Mouse corneal transplant model Protective [300,304] Rat and mouse lung transplant models Protective [207,241] Rat and mouse cardiac transplant model Protective [301][302][303] Mouse bone marrow transplant model Protective [306,307] Mouse skin transplant model Protective [310] Chimaeric humanised mouse model of graft arteriosclerosis Rat monocrotaline-induced pulmonary hypertension Protective [54] Angiotensin II-induced vascular constriction in rats Protective [41] Angiotensin II-induced vascular constriction in mice Protective [54], harmful [183] LPS-induced endotoxaemia Protective [182] Cataracts Mice overexpressing human IDO1 in the lens Harmful [591] Bone remodelling Wild-type mice Protective [592,593] maintenance of self-tolerance under normal conditions. However, numerous studies with Ido1 gene-deficient mice or IDO1 inhibitors reveal that the enzyme plays an important role in the establishment of acquired immune tolerance upon exposure to new or foreign antigens.…”
Section: Ido1 and Immune Regulation In Physiological And Disease Settmentioning
confidence: 99%
“…Two possible mechanisms of apoptosis are proposed: 1) depletion of tryptophan (de la Maza and Peterson, 1988;Ozaki et al, 1988;Lee et al, 2002;Platten et al, 2012) and 2) production of toxic tryptophan metabolites in the kynurenine pathway, such as kynurenines and 3-hydroxyanthranilic (3-HAA) (Morita et al, 2001;Fallarino et al, 2003;Mailankot et al, 2009;Lee et al, 2010;Mailankot and Nagaraj, 2010;Song et al, 2011;Hou et al, 2014). In this study, we demonstrated that the addition of either the IDO inhibitor 1-MT or L-tryptophan could decrease IFN-Îł-induced reduction of cell viability ( Figure 5A) and apoptosis ( Figure 5B-E).…”
Section: Discussionmentioning
confidence: 99%
“…To generate the double transgenic mice that specifically overexpressed hIDO and hSVCT2 in the lens epithelium and fiber cells, we cross-bred homozygous hIDO with homozygous hSVCT2 transgenic mice, both on a C57BL/6 background. The details for the hIDO mice have been published elsewhere (19). These animals contain high levels of kynurenines in the lenses.…”
Section: Methodsmentioning
confidence: 99%
“…The kynurenines in the mouse lens LMW fraction were determined using a GraceVydac C 18 column (4.6 Ï« 250 cm; 218TP54) in a high performance liquid chromatograph, which was run using a 0 -12% H 2 O-acetonitrile gradient at a flow rate of 0.8 ml/min with effluent monitoring at ex / em Ï­ 360/480 nm, as described previously (19). Kyn, Nfk, and 3OHKyn standard curves were generated under the same conditions to establish the levels of the kynurenines in the LMW fractions.…”
Section: Measurement Of Kynurenines In the Mouse Lmw Fraction-mentioning
confidence: 99%